State-of-the-art review on steel-concrete composite walls - Yu, Chao-Qun; Tong, Jing-Zhong; Zhou, Si-Ming; Zhang, Jia-Ming; Shen, Jia-Jia; Zhang, Lei; Tong, Gen-Shu; Li, Qing-Hua; Xu, Shi-Lang (Sustainable structures, 2024)
Steel-concrete composite walls, valued for their capacity to combine the strengths of steel and concrete, have become a prevalent construction choice. During the past few decades, the performance of steel-concrete composite walls has been studied by means of structural tests, theoretical analysis, and numerical simulation. Different types of steel-concrete composite walls have been proposed by researchers to satisfy miscellaneous structural requirements. Meanwhile, new forms were continually being developed to further improve the mechanical performance. This review paper examines research conducted over the past few years on these versatile structural elements. The paper categorizes steel-concrete composite walls according to the arrangement of steel plates and concrete, along with the configurations of steel plates. It delves into the unique characteristics of each type and analyzes their performance under various loading conditions, including axial, cyclic, shear, fire, dynamic, impact, and joint loads. Additionally, existing design recommendations for these walls are summarized. To conclude, the paper offers insights into potential future developments in steel-concrete composite wall technology.